Syntactic Contexts of Subordinators in Written Complex Sentences of Selected Students of English for Academic Purposes in Makurdi (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
The study assesses the syntactic contexts of subordinators in written complex sentences of selected students of English for Academic Purposes (EAP) in Federal University of Agriculture, Makurdi. The structural grammar description of the structural contexts of subordinators in modern English usage is foregrounded to provide the linguistic basis for assessment of the structural contexts of subordinators in the students’ written complex sentences. The model is used to design a proficiency assessment test tagged, Uses of subordinators in English. The study subjects are forty-nine students, randomly selected from an EAP lecture group in 2021/2022 academic session. The results of the data analysis, using frequency, percentage and mean statistics, indicate that the students are incapable of using simple, complex, correlative and marginal subordinators to generate complex sentences in English.  Specifically, the students can not construct complex sentences with after, once, that, unless, whereas, but that, except, in so much as, as though, as...as, such…as, less…than, no sooner… than, scarcely…when, the…the, whether…or, even if…(yet), unless…than, seeing that…( therefore),if only, in spite of the fact that, who and when.The study recommends that the students should be taught  the structural contexts in which subordinators are employed in English complex sentences.
Keywords: subordinators; structural contexts; complex sentence construction; EAP students’ deficiencies